2008
DOI: 10.1016/j.jacc.2008.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Adrenergic Receptor Genotypes and Survival in Heart Failure Patients Treated With Carvedilol or Metoprolol

Abstract: Genotypes and haplotypes of ADRB1, ADRB2, and ADRA2C did not significantly affect survival in metoprolol-treated or carvedilol-treated HF patients in this study. These results complement the findings of 2 similarly designed previous studies, but do not replicate an association of ADRB2 haplotypes and survival. All 3 studies differ from a survival benefit reported for bucindolol-treated homozygous ADRB1 R389 individuals. This may be attributable to a drug-specific interaction between genotype and outcome with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 29 publications
(30 reference statements)
5
91
1
2
Order By: Relevance
“…Within the MERIT-HF enrollment criteria (BEST Comparison Group, BCG) the differential response between genotypes is even more pronounced, with an Arg/Arg versus Gly carrier hazard ratio of 0.59 (0.40, 0.87; Pϭ0.007) in the bucindolol group versus a nonsignificant hazard ratio of 1.02 in the placebo group. Another relatively large study (nϭ637) also has shown no ␤ 1 389 Arg versus Gly differentiation of clinical response to metoprolol, or carvedilol, 166 and there are no reports that metoprolol or carvedilol clinical end point responses are affected by the ␤ 1 389 Arg/Gly genotype. This likely means that the basis for bucindolol's differentiation is its unique pharmacological properties of ␤ 1 389 Arg inverse agonism 157 and NE lowering.…”
Section: Polymorphic Variation In ␤ 1 -And ␤ 2 -Arsmentioning
confidence: 99%
“…Within the MERIT-HF enrollment criteria (BEST Comparison Group, BCG) the differential response between genotypes is even more pronounced, with an Arg/Arg versus Gly carrier hazard ratio of 0.59 (0.40, 0.87; Pϭ0.007) in the bucindolol group versus a nonsignificant hazard ratio of 1.02 in the placebo group. Another relatively large study (nϭ637) also has shown no ␤ 1 389 Arg versus Gly differentiation of clinical response to metoprolol, or carvedilol, 166 and there are no reports that metoprolol or carvedilol clinical end point responses are affected by the ␤ 1 389 Arg/Gly genotype. This likely means that the basis for bucindolol's differentiation is its unique pharmacological properties of ␤ 1 389 Arg inverse agonism 157 and NE lowering.…”
Section: Polymorphic Variation In ␤ 1 -And ␤ 2 -Arsmentioning
confidence: 99%
“…No difference in survival rates Sehnert et al, 2008 Gene structure and proposed three-dimensional structure of G␤3 and its splice variants, G␤3s and G␤3s2. Top, the G␤3 gene consists of 11 exons; coding exons are indicated in black.…”
Section: Lobmeyer Et Al 2007mentioning
confidence: 99%
“…First, the as- sociation of these polymorphisms with heart failure susceptibility and prognosis is controversial. 11, 21 One possible reason for the inconsistencies between studies is the low sample numbers used, as in this study. The present results should be compared with those of larger studies.…”
Section: Study Limitationsmentioning
confidence: 91%